Brand Community Development Through Associated Communities: Grounding Community Measurement Within Social Identity Theory - Heere, Bob; Walker, Matthew; Yoshida, Masayuki; Ko, Yong Jae; Jordan, Jeremy S.; James, Jeffrey D. (Journal of marketing theory and practice, 2011)
The purpose of this study was to measure consumer identification with several (brand) communities using a multidimensional psychometric community identity instrument grounded in social identity theory. Use of such instrumentation allowed the authors to examine how consumer identification with associated communities affected identification with the brand community. Data were collected on four different community identities (college football team, university, city, state) among students at the three major Florida universities. Results indicated that identification with the respective teams was affected by identification with other communities surrounding the team. This interplay among community identities had a strong subsequent effect on consumer behavior.